Heat Shock Protein 70 and 90 Genes in the Harmful Dinoflagellate Cochlodinium polykrikoides: Genomic Structures and Transcriptional Responses to Environmental Stresses - Ruoyu Guo; Seok Hyun Youn; Jang-Seu Ki (International Journal of Genomics)
The marine dinoflagellate Cochlodinium polykrikoides is responsible for harmful algal blooms in aquatic environments and has spread into the world’s oceans. As a microeukaryote, it seems to have distinct genomic characteristics, like gene structure and regulation. In the present study, we characterized heat shock protein (HSP) 70/90 of C. polykrikoides and evaluated their transcriptional responses to environmental stresses. Both HSPs contained the conserved motif patterns, showing the highest homology with those of other dinoflagellates. Genomic analysis showed that the CpHSP70 had no intron but was encoded by tandem arrangement manner with separation of intergenic spacers. However, CpHSP90 had one intron in the coding genomic regions, and no intergenic region was found. Phylogenetic analyses of separate HSPs showed that CpHSP70 was closely related with the dinoflagellate Crypthecodinium cohnii and CpHSP90 with other Gymnodiniales in dinoflagellates. Gene expression analyses showed that both HSP genes were upregulated by the treatments of separate algicides CuSO4 and NaOCl; however, they displayed downregulation pattern with PCB treatment. The transcription of CpHSP90 and CpHSP70 showed similar expression patterns under the same toxicant treatment, suggesting that both genes might have cooperative functions for the toxicant induced gene regulation in the dinoflagellate.